2021
DOI: 10.1002/jsfa.11082
|View full text |Cite
|
Sign up to set email alerts
|

Influence of S. cerevisiae and P. kluyveri as starters on chocolate flavour

Abstract: BACKGROUND: Fermented cocoa beans (Theobroma cacao L.) are a pivotal raw material for chocolate production. A cocktail yeast applied in the cocoa fermentation process can promote the formation of pleasant metabolites. Saccharomyces, Pichia and Hanseniaspora have been widely used in fermentation to improve the final product organoleptic profile, highlighting that fermentation is a critical point for chocolate flavour precursor production. This study aims to evaluate the impact of Pichia kluyveri and Saccharomyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Overall, these findings suggested that the production of VOCs in the cocoa pulp-bean mass will not primarily depend on the presence of different S. cerevisiae strains but rather on the biochemical composition of the cocoa pulp (providing flavor precursors) or gene expression levels. Still, genomic comparison between strains of species of different yeast genera naturally occurring during cocoa fermentation processes, such as Hanseniaspora and Pichia , should be performed, as previous studies have demonstrated differential VOC productions according to the yeast species inoculated ( Díaz-Muñoz et al., 2021 ; Moreira et al., 2021 ). However, the single amino acid changes found in the acetyltransferases ATF1 and IMO32P, affecting strains from the West African fermented food cluster and West African cocoa cluster, respectively, may result in a different activity of those ester-synthesizing enzymes and, thus, may have an impact on the VOC production by S. cerevisiae cocoa strains.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these findings suggested that the production of VOCs in the cocoa pulp-bean mass will not primarily depend on the presence of different S. cerevisiae strains but rather on the biochemical composition of the cocoa pulp (providing flavor precursors) or gene expression levels. Still, genomic comparison between strains of species of different yeast genera naturally occurring during cocoa fermentation processes, such as Hanseniaspora and Pichia , should be performed, as previous studies have demonstrated differential VOC productions according to the yeast species inoculated ( Díaz-Muñoz et al., 2021 ; Moreira et al., 2021 ). However, the single amino acid changes found in the acetyltransferases ATF1 and IMO32P, affecting strains from the West African fermented food cluster and West African cocoa cluster, respectively, may result in a different activity of those ester-synthesizing enzymes and, thus, may have an impact on the VOC production by S. cerevisiae cocoa strains.…”
Section: Discussionmentioning
confidence: 99%
“…Using starter cultures [9,37,[58][59][60][62][63][64][65][66][67][68][69][70][71][72][73][74][75] Using enzymes [76- Given the important role of microorganisms in cocoa fermentation, several studies propose the use of starter cultures as a strategy to improve cocoa quality and maintain reproducibility among fermentation batches [8,[58][59][60]. Potential starter cultures have also been studied to elucidate microbial diversity, structure, and functional and metabolic pathways.…”
Section: Purpose How Referencesmentioning
confidence: 99%
“…The production of aromas during cacao fermentation has been mainly associated with the microbiological consortium of yeasts in the process (10,25,28,29). It is subjected to factors such as the nutrient concentration of the substrate, biochemical conditions of the process, and yeast genetics that, in turn, intervene in the production of enzymes and generation of metabolites of interest, as expressed by Kongor et al ( 30) and Moreira et al (31). The aroma production test in the cacao pulp substrate of the yeasts under study is shown in Figure 6 through the aroma profile of the musts.…”
Section: Production Of Yeast Aromas In Cacao Pulp Mustsmentioning
confidence: 99%